The Learning Model M-learning: the Harmonization between Education System and New Emerging Technologies - Guevara Roa, Elizabeth (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
M-learning is presented as a response to the constant technological modifications emerging in our time, such changes are potential candidates to improve the traditional education system.Today, there are still some current models used in the traditional education system that have become obsolete due largely to lack of renovation and engaging emerging technologies of our time. In today's worldthe student has to reach a lot of information which was previously difficult to access, however, the challenge is now, not only focuses on the approach to such information, but that the student is ready to analyze it and use it properly in the present.Within this panorama, the mobile e-learning (m-learning) is a response to the constant technological changes emerging in the world, taking into account these changes renewed and enriched education resulting in better development and preparation of students obtained .To support this, several case studies are analyzed in different educational levels where the m-learning is applied as an effective learning strategy, it seeks to publicize the advantages and disadvantages posed by the use of such technology, and identifying the challenges that are needed to address.Furthermore, data were also collected through the application of a survey on the state of Veracruz in Mexico, in different high schools about using mobile devices, the method to use is judgmental sampling, with the aim of finally establish proposals to achieve a successful implementation of m-learning.As a last step, in order to measure the effectiveness of the given proposals, they are applied in a case of study conducted within a secondary school, also in the state of Veracruz in Mexico.